Synthesis and Antibacterial Activity of Chalcones and Pyrimidine-2-ones - A. K. Parekh; K. K. Desai (E-Journal of Chemistry)
Some new chalcones have been prepared by Claisen-schmidt condensation of ketone and different aromatic aldehydes. These chalcones on condensation with urea in presence of acid gave Pyrimidine-2-ones. The synthesized compounds have been characterized by elemental analysis, IR and 1H NMR spectral data. They have been screened for their antibacterial activity against Gram positive bacteria B. subtillis & S. aureus and Gram negative bacteria E. coli & S. typhi.